2010
DOI: 10.1039/c0nr00193g
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-dominated controllable biomimetic synthesis of gold nanoparticles in a quasi-biological system

Abstract: A new biomimetic strategy of creating a quasi-biological system (an aqueous solution containing electrolytes, peptide, enzyme and coenzyme) for the preparation of gold nanoparticles with uniform and tunable sizes has been put forward and validated, adopting environmentally-friendly reducing agents and a biocompatible capping ligand in aqueous solution at room temperature. The biomimetic synthetic route has the characteristics for good stability of the resulting AuNPs capped with glutathione via strong Au-S bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
1
16
0
2
Order By: Relevance
“…This study strengthened the role of glutathione synthesis pathway in the intracellular formation of CdSe QDs. The route involving the intracellular formation of CdSe QDs has also been applied toward the directional synthesis of other hetero nanostructures such as Au NPs, Au-Ag alloy NPs, Au clusters, PbSe nanocubes, and Ag 2 Se QDs (Cui et al, 2010(Cui et al, , 2012Zhang et al, 2011;Gu et al, 2012). This implies the significant importance of this biosynthetic route in tailored biogenesis of nanostructures in other microorganisms.…”
Section: Genetic Tuning Of Quantum Dotsmentioning
confidence: 99%
“…This study strengthened the role of glutathione synthesis pathway in the intracellular formation of CdSe QDs. The route involving the intracellular formation of CdSe QDs has also been applied toward the directional synthesis of other hetero nanostructures such as Au NPs, Au-Ag alloy NPs, Au clusters, PbSe nanocubes, and Ag 2 Se QDs (Cui et al, 2010(Cui et al, , 2012Zhang et al, 2011;Gu et al, 2012). This implies the significant importance of this biosynthetic route in tailored biogenesis of nanostructures in other microorganisms.…”
Section: Genetic Tuning Of Quantum Dotsmentioning
confidence: 99%
“…然后, 构建简便的模拟体系, 即"准生物体系", 更好 图 6 细胞信标构建生物检测探针的原理及其应用 [34] (网络版彩图) http://engine.scichina.com/doi/10.1360/N032015-00162 图 7 细胞信标的优良特性 [34] (网络版彩图) 地实现生物标记纳米材料合成的控制. 近年来, 通过 模拟胞内的生化反应途径, 在胞外构建了由金属离 子、酸根离子、氨基酸、多肽、辅酶和酶等共同组成 的无机纳米材料的"准生物合成体系", 即直接在溶 液中耦合不同生化反应, 实现 Au 纳米颗粒 [78] 、Au 团簇 [79,80] 、 Au-Ag 合晶纳米颗粒 [81] 、 PbSe 纳米立方 [82] 以及近红外 Ag 2 Se 量子点 [10] 的胞外可控合成. 准生物体系合成 Au 纳米颗粒时, 仅通过改变还 原剂辅酶 NADPH 的用量, 就可以合成不同粒径的纳 米金 [78] .…”
Section: 准生物体系可控合成生物标记纳米材料unclassified
“…近年来, 通过 模拟胞内的生化反应途径, 在胞外构建了由金属离 子、酸根离子、氨基酸、多肽、辅酶和酶等共同组成 的无机纳米材料的"准生物合成体系", 即直接在溶 液中耦合不同生化反应, 实现 Au 纳米颗粒 [78] 、Au 团簇 [79,80] 、 Au-Ag 合晶纳米颗粒 [81] 、 PbSe 纳米立方 [82] 以及近红外 Ag 2 Se 量子点 [10] 的胞外可控合成. 准生物体系合成 Au 纳米颗粒时, 仅通过改变还 原剂辅酶 NADPH 的用量, 就可以合成不同粒径的纳 米金 [78] . 利用准生物体系较温和的还原氛围, 可以合 成尺寸分布较窄、粒径均一且稳定性好的 Au-Ag 合 晶纳米颗粒, 通过改变 Au、Ag 前体的比例, 可以实 现其粒径的调控 [81] .…”
Section: 准生物体系可控合成生物标记纳米材料unclassified
“…Previous studies indicated that a appropriate stabilizer, mild reductant and gold precursor in the appropriate valence state play key roles in the synthesis of AuNCs. 16,20,21 In this work, WGA was chosen as the reducing and capping agent because the rich tyrosine residues (4.1%) of WGA can reduce a Au(III) or Au(I) complex at pH > 10 and the rich cysteine residues (18.4%) of WGA can subsequently bind to the reduced gold atoms via Au-S bonds to form stabilized nanoclusters. 16 In the preparation of AuNCs, the Au(I) complex was incubated with WGA at pH ∼ 12.2 under vigorous stirring at 37 °C.…”
Section: Synthesis and Characterization Of Fluorescent Au 25 Ncsmentioning
confidence: 99%